Sagittal and Partial Coronal Synostosis, Treated by Modified Pi Procedure with Barrel Stave Osteotomy : Report of One Case (Bangladesh Journal of Neurosurgery, 2020)
Craniosynostosis consists ofprematurefusion of cranial suture(s) resulting inabnormalhead shape.Sagittalcraniosynostosis involves premature closure ofthe sagittal suture,producing an abnormallyelongated skull called scaphocephaly. Multiple techniquesand their modifications have been used forthe correction of sagittal craniosynostosis.We present a case of sagittal and partial coronal craniosynostosis who was treatedwith Modified Piprocedure with barrel stave osteotomy.Bang. J Neurosurgery 2020; 9(2): 151-155